2021
DOI: 10.1001/jamacardio.2021.2065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Clinical and Subclinical Myocarditis in Competitive Athletes With Recent SARS-CoV-2 Infection

Abstract: This cohort study assesses the prevalence of myocarditis in athletes with COVID-19 and compare screening strategies for safe return to play.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
301
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(346 citation statements)
references
References 36 publications
(90 reference statements)
14
301
1
4
Order By: Relevance
“…This is in concordance with the cohort study of Daniels et al of 1597 US competitive athletes with CMR screening after COVID-19 infection. They confirmed the role of CMR imaging for the detection of clinical and subclinical myocarditis in 2.3% of college athletes after COVID-19 infection [10].…”
Section: Discussionsupporting
confidence: 54%
“…This is in concordance with the cohort study of Daniels et al of 1597 US competitive athletes with CMR screening after COVID-19 infection. They confirmed the role of CMR imaging for the detection of clinical and subclinical myocarditis in 2.3% of college athletes after COVID-19 infection [10].…”
Section: Discussionsupporting
confidence: 54%
“…In a cohort of 145 subjects, Starekova and colleagues [ 3 ] observed that only 2 athletes (1.4%) showed CMR evidence of acute inflammation. Furthermore, in a cohort performed on 1597 after COVID-19 infection, CMR screening detected 37 subjects (2.3%) with clinical and subclinical myocarditis [ 33 ], and recent data from a multi-centered prospective study reported that the prevalence of myocarditis following SARS-CoV-2 infection is about 0–5–3% and no adverse cardiac events were registered during a median follow-up of 113 days in young competitive athletes with RMN signs of myocarditis [ 34 ]. Other studies evaluating symptom persistence in adults with mild COVID-19 disease reported that, during three-to-six month follow-up palpitations, chest pain and dyspnea were present, respectively in 9, 5 and 30% of adults [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigators found that 46% had mild to moderate symptoms of COVID-19 infection and that 54% were asymptomatic. Twelve athletes (46%) had myocardial LGE, with 4 (15%) having myocarditis-like findings on CMR ( 52 ).…”
Section: Evaluation Of Athletes After Covid-19mentioning
confidence: 99%
“…#) Patient Cohort (Cases) LGE Positive Abnormal T 1 + T 2 , Myocarditis-like Findings on CMR a LGE Pattern/Location in Patients With Myocarditis a , b Troponin in Patients With Myocarditis a ECG and TTE in Patients With Myocarditis a Pericardium Pathology n Men, % Age, y Rajpal et al ( 52 ) 26 58 19 ± 1.5 12/26 (46) 4/26 (15%) 2 asymptomatic 2 symptomatic Epicardial, segments 3 and 9 Patchy, segments 3 and 9 Patchy, segments 2, 3, 8, and 9 Linear, segments 8 and 9 No No Effusion: 2/26 (8%) in athletes with myocarditis a 54% asymptomatic, 46% mild to moderate symptoms CMR 11-53 d after positive test result Brito et al ( 54 ) 54 (48 c ) 85 19 (19-21) 1/48 (2) 0% not applicable not applicable not applicable Pericardial LGE: 19/48 (40%) Effusion: 28/48 (58%) 30% asymptomatic, 66% mild symptoms, 4% moderate symptoms CMR 27 (range 22-33) days after positive test result Małek et al ( 55 ) 26 19 24 (21-27) 1/24 (4) 0% not applicable not applicable not applicable Effusion: 2/26 (8%) …”
Section: Evaluation Of Athletes After Covid-19mentioning
confidence: 99%